GONADORELIN INJECTION DURING ESTRUS ON FOLICLE DEVELOPMENT AND OVULATION AND NON-RETURN RATE IN BALI CATTLES THAT EXPERIENCE REPEATED BREEDING - Suputra, Gusde Wahyu Krisna; Trilaksana, I Gusti Ngurah Bagus; Pemayun, Tjok Gde Oka; Sukernayasa, I Wayan; Widiarta, I Nyoman Oka (Buletin Veteriner Udayana, 2023)
This study aims to prove that gonadorelin administration is able to cause follicle development to reach follicles that are ready to be ovulated and ovulation and fertilization occurs in bali cattle that experience repeated breeder in Sobangan Village, Badung Regency, Bali. Observations of developing follicles and the timing of ovulation were performed using transrectal ultrasound via rectal palpation. The design used in this study was a completely randomized design (CRD) consisting of three treatment groups, namely the control group without gonadorelin injection (P0), the group receiving 50 g/im/head injection of gonadorelin (P1) and the group receiving 50g/im/head injection. gonadorelin injection at a dose of 100g/im/head (P2). Gonadorelin injection was performed when clear discharge came out of the vagina as a sign of the appearance of estrus and all samples in IB at 12 hours after the appearance of estrus. The results showed that the average follicle diameter at the time of estrus in the P0 group was 7.37 + 0.46mm, the P1 group was 7.67 + 0.78mm, and the P2 group was 7.59 + 0.77mm and statistically did not show any difference. which meaningful (P> 0.05). When reaching the de graff follicle, the mean follicle diameter in the P0 group was 11.27 + 0.59mm, the P1 group was 10.08 + 0.60mm, the P2 group was 9.92 + 1.06mm statistically showed a significant difference (P<0.05). At ovulation the mean follicle diameter in the P0 group was 10.53 + 0.57mm, in the P1 group 9.51 + 0.59mm, in the P2 group 9.33+0.89mm, statistically showed a significant difference (P<0.05). Ovulation time in the P0 group was 71.56 + 1.33 hours, while for the P1 and P2 groups it was 12.00 + 0.00 hours and statistically showed a significant difference (P<0.05). The percentage of non-return rates in the three treatment groups were 0%, 77.8% and 88.9%, for P0, P1 and P2, respectively.